An Error Analyis on Written Production Made by EFL Students of International Program of Muhammadiyah University of Surakarta - Suhono, Suhono, Dr. Dwi Haryanti, M.Hum, Agus Wijayanto, Ph.D (2015)
The aim of this study is to develop further analyzing of error analysis in second language learners of international program of Muhammadiyah University of Surakarta. The researcher explored the type of grammatical errors made by students at different proficiency levels: high, medium, and low level. More specifically, this study was an attempt to describe the type of grammatical error which frequently exist in written production, to describe frequency grammatical error among proficiency levels, and to describe the students' understanding of errors. Students' writings were analyzed for errors based on surface strategy taxonomy. The results of this research revealed that 846 sentences indicated errors. Types of omission error was the highest one 322 (37.9%) sentences. Afterward, grammatical error in low proficiency level was the highest one 322 (37.9%) sentences. The second was high proficiency level 276 (32.6%) sentences. The third was medium proficiency level 248 (29.3%) sentences. Most of the students didn't understand about grammatical errors, because through 30 students' interview only 7 students were able to change grammatical error to be good sentences.